Are objective data an appropriate replacement for subjective data in site choice analysis?. Issue 2 (3rd April 2019) - Deely, John; Hynes, Stephen; Curtis, John
ABSTRACT: Random utility theory is founded on the concept that an individual selects the alternative that gives them the highest level of utility, given the individual's preferences and perception of a good. Discrete choice analysis, however, seldom uses an individual's perception of a good, instead, more convenient objective data are employed. This paper aims to explore the viability of objective data as a suitable replacement for subjective data in recreational site choice modelling. Random parameter logits are applied to coarse angling site choice data where two site attribute data sets are used; the first is comprised of users' perception of the site attributes and the second is composed of fishery managers' perspective of those same attributes. The results reveal that models based on the subjective data outperform those of the objective data. The derived welfare estimates indicate a divergence between the two sources of data in terms of the magnitude of the estimates but not direction. Further analysis is conducted to determine if the manager's objective ratings are measuring the sites using a similar set of criteria as the user's subjective ratings. The results suggest that the managers' perspective is closely aligned with the anglers' who frequent the sites most often.